Long-term management of Fontan patients: The importance of a multidisciplinary approach - Martino, Diletta; Rizzardi, Caterina; Vigezzi, Serena; Guariento, Chiara; Sturniolo, Giulia; Tesser, Francesca; Salvo, Giovanni di (Frontiers in Pediatrics, 2022)
The Fontan operation is a palliative procedure that leads to increased survival of patients with a functional single ventricle (SV). Starting from 1967 when the first operation was performed by Francis Fontan, more and more patients have reached adulthood. Furthermore, it is expected that in the next 20 years, the population with Fontan circulation will reach 150,000 subjects. The absence of right ventricular propulsion and the inability to improve cardiac output because of the low cardiac reserve are the main issues with the Fontan circulation; however, potential complications may also involve multiple organ systems, such as the liver, lungs, brain, bones, and the lymphatic system. As these patients were initially managed mainly by pediatric cardiologists, it was important to assure the appropriate transition to adult care with the involvement of a multidisciplinary team, including adult congenital cardiologists and multiple subspecialists, many of whom are neither yet familiar with the pathophysiology nor the end-organ consequences of the Fontan circulation. Therefore, the aim of our work was to collect all the best available evidence on Fontan's complications management to provide “simple and immediate” information sources for practitioners looking for state of the art evidence to guide their decision-making and work practices. Moreover, we suggest a model of follow-up of patients with Fontan based on a patient-centered multidisciplinary approach.